CADMIUM-INDUCED PHYSIOLOGICAL AND GENOTOXIC ALTERATIONS IN Bryophyllum daigremontianum - (:unkn) unknown (GLOBAL NEST, SECRETARIAT, 2013)
When evaluating the negative impacts of heavy metals in the environment, plants can be used as biological indicators in assessing damage done by bio-accumulation of heavy metals. For detecting the genotoxic effects of heavy metals, the RAPD-PCR technique is applied in plants. In this study, Blyophyllum daigremontianum was used as a bio-indicator for Cadmium (Cd) pollution. B. daigremontianum plantlets were obtained from bulbiliferous spurs. They were grown singly in standard pots and each of the experimental groups of 5 replicates were watered daily with Hoagland solution (20 ml) containing 0, 50, 100, 200 and 400 mu M Cd for two months. Plantlets were harvested at the end of the two-month experimental period and photosynthetic pigment (chlorophyll a, chlorophyll b, total chlorophyll, chlorophyll a/b and carotenoids) contents of B. daigremontianum in response to Cd stress were investigated. The comparison between unexposed and exposed B. daigremontianum groups revealed gradual reductions of photosynthetic pigment contents (-40.57% for chlorophyll a, -37.63% for chlorophyll b, -36.27% for total chlorophyll, -20.58% for chlorophyll a/b and -37.66% for carotenoids) at 400 pM and a genomic instability as Cd concentration increases. The results indicated that changes in RAPD-PCR profiles following Cd treatments included a variation in band intensities, a loss of normal bands, and the appearance of new bands compared to unexposed plantlets. Cd concentrations of the collected samples were measured by employing ICP-OES during the study. The concentrations of Cd at 400 mu M Cd treatment were increased significantly in leaves (-5.03 fold), stems (-6.28 fold) and roots (-3.90 fold) of B. daigremontianum. The present study evidences that as an investigation tool for environmental toxicology, the RAPD technique can be useful and can be applied as a suitable biomarker assay for the detection of genotoxic effects of Cd pollution on plants.
Keywords: Kalanchoe daigremontiana; RAPD-PCR; genotoxicity; heavy metals; AMPLIFIED POLYMORPHIC DNA; WATER RELATIONS; RAPD ANALYSIS; PLANTS; GROWTH; ACCUMULATION; STRESS; DAMAGE; SATIVUM; TOBACCO